2014
DOI: 10.4291/wjgp.v5.i3.293
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to anti-tumor necrosis factor therapy in ulcerative colitis

Abstract: Ulcerative colitis (UC) is an immune-mediated, chronic inflammatory disease of the large intestine. Its course is characterized by flares of acute inflammation and periods of low-grade chronic inflammatory activity or remission. Monoclonal antibodies against tumor necrosis factor (anti-TNF) are part of the therapeutic armamentarium and are used in cases of moderate to severe UC that is refractory to conventional treatment with corticosteroids and/or immunosuppressants. Therapeutic response to these agents is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…[19] Previous studies have identified several clinical or biological factors influencing response to anti-TNF in UC, such as severity of the disease, younger age, duration of colitis or extensive colitis. [20] In our study, we found that extraintestinal manifestations, ongoing topical steroids and 5-ASA at baseline were significantly associated with the absence of clinical remission in patients with refractory UP. Another recent study also identified extraintestinal manifestation as a risk factors for colectomy in patients with UC on thiopurine treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 47%
“…[19] Previous studies have identified several clinical or biological factors influencing response to anti-TNF in UC, such as severity of the disease, younger age, duration of colitis or extensive colitis. [20] In our study, we found that extraintestinal manifestations, ongoing topical steroids and 5-ASA at baseline were significantly associated with the absence of clinical remission in patients with refractory UP. Another recent study also identified extraintestinal manifestation as a risk factors for colectomy in patients with UC on thiopurine treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 47%
“…While antibodies against IFX are associated with loss of response [3], they are not suitable to predict response in IFX-naive patients. Recently, in addition to routine laboratory indicators and immune markers [4] much research activity focused on the measurement of gene expression values in colon biopsy samples and peripheral blood to predict the individual response to IFX in IFXnaive IBD patients. However, study designs including methods used to determine gene expression and patient populations to be enrolled were quite heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the immunological as well as genetic factors involved in a therapy re-fractory course of IBD are poorly understood and the relevance of reduced therapeutic response for the strength of the models phenotype still has to be determined. Finally, we were able to reproduce differentiation efficiency of previous publications [69,82] using the diseased cell lines. There were no observable differences in the organoids generated by treatment with the two different mid-/hindgut formation media and patient-derived organoids compared to control organoids from healthy donors, indicating that gut development is not obviously altered within the patient-derived organoids [69].…”
mentioning
confidence: 86%